Decline in Child Marriage and Changes in Its Effect on Reproductive Outcomes in Bangladesh - Kamal, SM Mostafa (Journal of Health, Population and Nutrition, 2012)
This paper explores the decline in child marriage and changes in its effect on reproductive outcomes of Bangladeshi women, using the 2007 Bangladesh Demographic and Health Survey data. Chi-square tests, negative binomial Poisson regression and binary logistic regression were performed in analyzing the data. Overall, 82% of women aged 20-49 years were married-off before 18 years of age, and 63% of the marriages took place before 16 years of age. The incidence of child marriage was significantly less among the young women aged 20-24 years compared to their older counterparts. Among others, womens education appeared as the most significant single determinant of child marriage as well as decline in child marriage. Findings revealed that, after being adjusted for sociodemographic factors, child marriage compared to adult marriage appeared to be significantly associated with lower age at first birth (OR=0.81, 95% CI=76-0.86), higher fertility (IRR=1.45, 95% WCI=1.35-1.55), increased risk of child mortality (IRR=1.64, 95% WCI=1.44- 1.87), decreased risk of contraceptive-use before any childbirths (OR=0.56, 95% CI=0.50-0.63), higher risk of giving three or more childbirth (OR=3.94, 95% CI=3.38-4.58), elevated risk of unplanned pregnancies (OR=1.21, 95% CI=1.02-1.45), increased risk of pregnancy termination (OR=1.16, 95% CI=1.00-1.34), and higher risk of the use of any current contraceptive method (OR=1.20, 95% CI=1.06-1.35). Increased enforcement of existing policies is crucial for the prevention of child marriage. Special programmes should be undertaken to keep girls in school for longer period to raise the age of females at first marriage in Bangladesh and thereby reduce the adverse reproductive outcomes. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12296 J HEALTH POPUL NUTR 2012 Sep;30(3):317-330